Suicide. - Hawton, K; van Heeringen, K (2009)
Suicide receives increasing attention worldwide, with many countries developing national strategies for prevention. Rates of suicide vary greatly between countries, with the greatest burdens in developing countries. Many more men than women die by suicide. Although suicide rates in elderly people have fallen in many countries, those in young people have risen. Rates also vary with ethnic origin, employment status, and occupation. Most people who die by suicide have psychiatric disorders, notably mood, substance-related, anxiety, psychotic, and personality disorders, with comorbidity being common. Previous self-harm is a major risk factor. Suicide is also associated with physical characteristics and disorders and smoking. Family history of suicidal behaviour is important, as are upbringing, exposure to suicidal behaviour by others and in the media, and availability of means. Approaches to suicide prevention include those targeting high-risk groups and population strategies. There are, however, many challenges to large-scale prevention, especially in developing countries.